If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7p = 8p + 1 Reorder the terms: 7p = 1 + 8p Solving 7p = 1 + 8p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-8p' to each side of the equation. 7p + -8p = 1 + 8p + -8p Combine like terms: 7p + -8p = -1p -1p = 1 + 8p + -8p Combine like terms: 8p + -8p = 0 -1p = 1 + 0 -1p = 1 Divide each side by '-1'. p = -1 Simplifying p = -1
| 81x+15=4-48x | | 235.99c-49.99=12 | | 500x-100x=y | | 3(u-2)-9=-3(-6u+7)-u | | y-5=6x | | 2x+2(x+1)=3 | | 19x=6x | | 6y^2-7y-3= | | 2x+5x+3=17 | | 235.99c+49.99=12 | | 3(c+2)+1c+1=57 | | 5x+5=8x-20 | | 5x/3=7/12 | | 6x+6-2x-14=7 | | 5p-7=2(2p-7) | | 4(x-3)=3(x-5) | | -2(3x-5)+5x=8+3(3x-2) | | 6+3(5x-5)=6-4(2x+1) | | 10*n=1 | | 4x-2+6(x-4)=3+2x | | 9(7x-2)= | | 3x(x+10)+4(x+20)+5x=185-3x | | 5n-14=41 | | 4*n=1 | | 2(2y-1)+y=3 | | 2(x+4)=2(-8-x)-2x | | (2x+3)x=50 | | 13-6d/7=7 | | 2+3q=4q | | B+1=-5b+5 | | -8(32x+13)=26(16-6x) | | 2+2x-5=5(x+3) |